Idolatry and the construction of the Spanish empire - Jordán, Mina García, 1972- (University Press of Colorado, 2018)
An ethnohistory on the spiritual and governmental conquest of the Indigenous people in colonial Mexico, Idolatry and the Construction of the Spanish Empire examines the role played by the shifting concept of idolatry in the conquest of the Americas, as well as its relation to the subsequent construction of imperial power and hegemony. Contrasting readings of evangelization plays and chronicles from the Indies and legislation and literature produced in Spain, author Mina García Soormally places theoretical analysis of state formation in Colonial Latin America within the historical context. The conquest of America was presented, in its first instances, as a virtual extension of the Reconquista, which had taken place in Spain since 711, during which Spaniards fought to build an empire based in part on religious discrimination. The fight against the "heathens" (Moors and Jews) provided the experience and mindset to practice the repression of the other, making Spain a cultural laboratory that was transported across the Atlantic Ocean. This book is an explication of religious orthodoxy and unorthodoxy during Spain's medieval and early modern period as they relate to idolatry, with analysis of events that occurred on both sides of the Atlantic.